The Eocene Hieroglyphic beds and Green shales in the Rożnów Lake area (Silesian Nappe, Outer Carpathians) - facies development and biostratigraphy - Waśkowska, Anna Elżbieta (Geology, Geophysics and Environment, 2014)
In the lithostratigraphic section of a sedimentary sequence of the Silesian Nappe in the area of Rożnów Lake, the strata that occur above the Ciężkowice sandstone and below the Globigerina marls are represented by a relatively thin unit informally named the Hieroglyphic beds and a succeeding thick complex of so-called Green shales. The Hieroglyphic beds, deposited over a short time interval during the Lutetian time (Reticulophragmium amplectens zone), are followed by the Green shales that were deposited from the Lutetian to the Priabonian (Reticulophrgamium amplectens, Ammodisus latus, Reticulophragmium rotundidorstum zones). This work describes the foraminiferal assemblages, on the basis of which, the age of the Green shales was established that in the area of Rożnów Lake. Deposition of the Green shale unit started in the Lutetian, while in other regions of the Silesian Basin it is documented from the Priabonian. The upper boundary of the Green shales is isochronous and defined by the base of the calcareous horizon of a specific type of marls known as the Globigerina marls.